Outcomes of femtosecond laser–assisted cataract and refractive lens surgery in patients with prior radial keratotomy. Issue 4 (April 2022) - Trinh, Tanya; Solomon, Benjamin; Mimouni, Michael; Cohen, Eyal; Gouvea, Larissa; Santaella, Gisella; Sorkin, Nir; AlShaker, Sara; Din, Nizar; Rootman, David S.
Abstract : FLACS- or FL-assisted RLE surgery in RK patients has a high risk for anterior capsule tears and should be avoided. Thickened incisional scars are potential sources of incomplete laser penetrance. Abstract : Purpose: To investigate outcomes of femtosecond laser (FL)-assisted cataract surgery (FLACS) and refractive lens exchange (RLE) in patients with prior radial keratotomy (RK). Setting: Single clinical practice. Design: Retrospective observational case series. Methods: All patients with prior RK undergoing FLACS- or FL-assisted RLE surgeries over a 6-year period were reviewed. Inclusion criteria were diurnal stability and stable manifest refraction. Exclusion criteria were any other incisional corneal surgery, macular or glaucomatous pathology, or vision loss due to any other cause. Data collected included demographics, visual acuity, laser settings, and complications. Main outcome measures were intraoperative and postoperative complications and visual outcomes. Safety and efficacy indices were evaluated. Results: 16 eyes of 9 patients were included. Mean age and follow-up time were 59.9 ± 9.9 years (range 44 to 75 years) and 3.3 ± 2.5 months, respectively. The mean number of RK cuts was 11.8 ± 5.3 (range 8 to 20). Mean preoperative uncorrected (UDVA) and corrected distance visual acuity (CDVA) were 0.9 ± 0.4 logMAR (Snellen 20/160) and 0.2 ± 0.3 logMAR (Snellen 20/30), respectively. 2 intraoperative anterior capsule tears were identified. 1 postoperative intraocular lens dislocation occurred. Postoperatively, the mean UDVA and CDVA were 0.2 ± 0.2 logMAR (20/30) and 0.1 ± 0.1 logMAR (20/25), respectively. The safety index was 1.6, and the efficacy index was 1.2. Conclusions: FLACS- or FL-assisted RLE surgery in RK patients has a high risk for anterior capsule tear and should be avoided. Thickened incisional scars are potential sources of incomplete laser penetrance. Toric lens implantation in RK eyes provide unpredictable astigmatic correction and should also be avoided.